(untitled) (Doctor Virtualis, 2024)
The cosmic order represents the focal point of reference for moral agents, who must evaluate their choices based on the degree of perfection rather than settling for inferiour objects or beings. According to Augustine of Hippo, justice is the virtue of ordered choice. The present contribution aims to show how, from the viewpoint of the creature, the structure of ordered choice does not change even when the theology of grace is developed in Ad Simplicianum. In particular, the essay focuses on the shift from an earlier view, developed before 397, that places the original cause of good will in the creature itself, along with God’s assistance, to a later and more radical perspective that sees God’s role as the exclusive source of good will through efficient and predestined intervention. The latter viewpoint has the dual advantage of unfolding some paradoxes of the previous perspective, while still maintaining the (ordered) form of justice, although it inevitably limits the role of creatures in relation to their merits.